Akibat Penggolongan Peran Seks pada Remaja - Jumadilla Afifah; Alya Arrahmah; Riska Mulyana; Linda Yarni (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
. Sex role classification in adolescents can have a significant impact on their development and well-being. While this classification can provide a framework for understanding gender identity, it can also limit possibilities for exploration and result in high conformity pressure. Adolescents may feel bound to narrow gender stereotypes, causing restrictions in self-expression and opportunities available to them. Impacts include increased risk of mental disorders, discrimination and stigma. To facilitate positive growth, it is important for society to recognize and support the diversity of gender identities, and provide space for adolescents to explore their interests, talents and aspirations without the restrictions imposed by gender stereotypes.